Identifying opportunities to improve governance of aquatic agricultural systems through participatory action research - Apgar, J.M.; Cohen, Philippa J.; Ratner, B.D.; de Silva, Sanjiv; Buisson, Marie-Charlotte; Longley, Catherine; Bastakoti, Ram C.; Mapedza, Everisto D. (Resilience Alliance, Inc., 2017)
Challenges of governance often constitute critical obstacles to efforts to equitably improve livelihoods in social-ecological systems. Yet, just as often, these challenges go unspoken, or are viewed as fixed parts of the context, beyond the scope of influence of agricultural, development, or natural resource management initiatives. What does it take to get governance obstacles and opportunities out in the open, creating the space for constructive dialogue and collective action that can help to address them? We respond to this question by comparing experiences of participatory action research (PAR) in coastal and floodplain systems in four countries (Zambia, Solomon Islands, Bangladesh, and Cambodia) with a focus on understanding how to build more equitable governance arrangements. We found that governance improvement was often an implicit or secondary objective of initiatives that initially sought to address more technical natural resource or livelihood-related development challenges. We argue that using PAR principles of ownership, equity, shared analysis, and feedback built trust and helped to identify and act upon opportunities to address more difficult-to-shift dimensions of governance particularly in terms of stakeholder representation, distribution of authority, and accountability. Our findings suggest that the engaged and embedded approach of researcher-facilitators can help move from identifying opportunities for governance change to supporting stakeholders as they build more equitable governance arrangements.